Implementasi Edu-Quizzer dalam meningkatkan antusiasme belajar pada mata pelajaran Al-Qur’an Hadits kelas X - Mahmudah, Ni’matul (Maliki Interdisciplinary Journal, 2024)
This study aims to explore how the use of interactive PowerPoint-based Edu-Quizzer media can enhance student enthusiasm in learning Al-Qur’an and Hadith in Grade X at MA Unggulan KH. Abdul Wahab Hasbulloh Jombang. The research employs a descriptive qualitative approach, using data collection techniques such as library research, observation, and documentation. The PowerPoint-based Edu-Quizzer media is designed to provide a more interactive and engaging learning experience for students. The findings show that the use of this media significantly increases student enthusiasm, as evidenced by higher active participation and increased interest in the learning material. Students are more engaged in the teaching and learning process. Additionally, the Edu-Quizzer media aids teachers in delivering material more effectively and enjoyably, creating a more dynamic and conducive classroom atmosphere for learning. Therefore, the use of interactive media like PowerPoint-based Edu-Quizzer not only boosts students’ enthusiasm for learning but also encourages deeper engagement and interaction during the learning process, ultimately supporting the achievement of better educational outcomes.